APE1/Ref-1 as a Serological Biomarker for the Detection of Bladder Cancer - Shin, Ju Hyun; Choi, Sunga; Lee, Yu Ran; Park, Myoung Soo; Irani, Kaikobad; Lee, Sang Do; Park, Jin Bong; Kim, Jin Man; Lim, Jae Sung; Jeon, Byeong Hwa (Cancer research and treatment, 2015)
Apurinic/apyrimidinic endonuclease 1/redox factor-1 (APE1/Ref-1) is a multifunctional protein that shows elevated expression in a number of cancers. We attempted to determine whether serum APE1/Ref-1 is elevated in patients with bladder cancer. Serum APE1/Ref-1 levels were determined using enzyme-linked immunosorbent assay in serum from patients with bladder cancer who had not received chemotherapy or radiotherapy (n=51) and non-tumor controls (n=55). The area under the receiver operating characteristic area under the curve was applied to determine the correlation between clinical factors and the serum levels of APE1/Ref-1. Serum levels of APE1/Ref-1 in bladder cancer patients were significantly elevated compared to those of the control group (3.548 ± 0.333 ng/100 μL [n=51] for bladder cancer vs. 1.547 ± 0.319 ng/100 μL [n=55] for the control group), with a sensitivity and specificity of 93% and 59%, respectively. Serum APE1/Ref-1 levels are associated with tumor stage, grade, muscle invasion, and recurrence. Serum APE1/Ref-1 might be useful as a potential serologic biomarker for bladder cancer.